The Effectiveness of Cooperative CTL Model Integrated with Qur’anic Values in Psychotropic Topic at MAN 4 Bantul - Kultsum, Qatrunnada Ummu; Sulistiyawati, Sulistiyawati (Proceeding International Conference on Religion, Science and Education, 2026)
This study aims to determine the effectiveness of the cooperative learning model with a Contextual Teaching and Learning (CTL) approach based on thematic Qur'anic verses on the learning outcomes and spiritual attitudes of students on the sub-subject of psychotropic drugs at MAN 4 Bantul. The type of research used is a quasi-experiment with a nonequivalent control group design. The research sample consisted of two 11th grade science classes, namely XI F1 as the control class (14 students) and XI F2 as the experimental class (13 students). The research instruments were a multiple-choice test consisting of 15 questions and a valid 28-item Likert scale questionnaire to measure spiritual attitudes. The results showed that the experimental class experienced an increase in learning outcomes with a moderate N-Gain score (0.43), while the control class only achieved a low score (0.25). The paired samples t-test showed a significant difference between the pretest and posttest in the experimental class (p < 0.001). Meanwhile, the average spiritual attitude score of the experimental class was higher than that of the control class. These findings indicate that the cooperative learning model with a CTL approach based on thematic Qur'anic verses has the potential to improve learning outcomes while fostering students' spiritual attitudes.